Humorns funktion i polisarbetet - Rolf Granèr (Nordisk Politiforskning)
Summary The purpose of this text is to discuss the function of police humour, especially in the group of patrolling policemen. The discussion is primarily based on a literature study combined with data from qualitative interviews and participant observations. Basically «joking relationships» are considered a form of play which gives the individuals involved a relative freedom from responsibility. In terms of dealing with frustration with work including resistance against authorities, internal joking can be considered a form of parenthesis behaviour, i.e. it expresses parts of the personality that are suppressed through demands of authoritative and correct behaviour in the outer world. Joking can be seen as a form of diversion, partly through making distance to anxiety provoking situations, partly through rejecting aggressive situations to more neutral ones. Furthermore joking is a way to devalue the world around, to idealize the police collective in order to relieve feelings of guilt, and enhance emotions of moral superiority. In terms of internal relationship joking can be seen as ways of strengthen group cohesion. This is done by marking a boundary to different outgroups. Humour can be a way of establishing norms and giving sanctions for non-accepted behaviours, to investigate what is accepted in the group, to express feedback, to deal with conflicts, distribution of power and status and a mean of socialisation of new members.